Contribution of Cost Accounting Information in Increasing Responsibility to Stake Holders in MSMES Lhokseumawe City - Auliyah Chairani; Dwi Rapika Putri; Putri Rama Dani; Munawar Khalil Nasution; M. Reihan; Muammar Gaddafi (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
The influence of accounting in countries, especially Indonesia, is currently experiencing rapid changes where the more the economic sector develops, the world will also become more advanced so that in the future various kinds of organizations such as companies will experience development. This research aims to test the influence of accounting cost in reminded not quite enough answer to stake holders in MSMEs in Lhoksemauwe City. The research method used in this research is the data collection method. The data collection method used is literature review, library research. Data collection methods in the library, reading, recording and managing research materials. The type of data used is data Qualitative. Results study it provides in-depth insight into how thoughtful integration between Cost Accounting, Responsibility and attention to Stakeholders can support the sustainable growth of MSMEs. The implications of these findings are not only relevant for practitioners and academics in the field of accounting, but can also be a basis for developing policies that support the holistic development of MSMEs.